The many not the few : the stolen history of the Battle of Britain - North, Richard D., 1946- (Continuum International Pub., 2012)
Immortalised in Churchill's often quoted assertion that never before was so much owed by so many to so few, the top-down narrative of the Battle of Britain has been firmly established in British legend. Britain was saved from German invasion by the gallant band of Fighter Command Pilots in their Spitfires and Hurricanes, and the public owed them their freedom. Richard North's radical re-evaluation of the Battle of Britain dismantles this mythical retelling of events. Taking a wider perspective than the much-discussed air war, North takes a fresh look at the conflict as a whole to show that the.